Pendidikan Kesehatan, Gizi Dan Perilaku Hidup Bersih Dan Sehat Bagi Anak Di Masa Pandemi Covid-19 Di Belawan Bahagia - Evanirwana Evanirwana (Ability: Journal of Education and Social Analysis, 2022)
On March 2019, Indonesia began to be exposed by covid-19 virus, not only Indonesia, but the whole world also exposed it. The pandemic caused by this virus has been going on for a year. It has a big impact on various sectors, including the economic and education sectors. In terms of economic sector, it can be seen that many employees have been laid off. Moreover, in terms of education, students are asked to study at home with their parents as an effort to break the covid-19 chain. Based on this problem, parents must familiarize children with healthy behavior, fulfill their nutritional needs and instill clean and healthy lifestyle for children so their immunity will be good and avoid the Covid-19 virus, another reason is that the habits given by the child will be carried until the child is an adult. This study uses a descriptive method, with data collection techniques using a survey in a google form, that is shared via WhatsApp. The data collection techniques using research instruments in the form of google form. The results of the collected data then the next step is to analyze and process it using simple statistics, namely the percentagethen entered into three categories; Good (B), Adequate (C) and Bad (Br). This study reveals that aspects of healthy behavior carried out by children with a percentage of 92% with good criteria, 88% fulfillment of nutrition with good criteria and 57% clean and healthy lifestyle with sufficient criteria. It can be concluded that the clean and healthy lifestyle aspect is not optimal because children are not used to sunbathing in the morning and using masks.